Operando ultrasonic monitoring of the internal temperature of lithium-ion batteries for the detection and prevention of thermal runaway - Owen, RE; Wiśniewska, E; Braglia, M; Stocker, R; Shearing, PR; Brett, DJL; Robinson, JB (Electrochemical Society, 2024)
Lithium-ion batteries (LIBs) play an integral role in powering various applications, from consumer electronics to stationary storage, and notably in the accelerating domain of electric vehicles (EVs). Despite their widespread adoption and numerous benefits, safety issues are of major concern, especially with the surge in their utilization and increasing proliferation of second-life cells, particularly in domestic energy storage applications. A critical concern revolves around susceptibility to thermal runaway, leading to highly hazardous and challenging-to-contain fires. Addressing these concerns necessitates effective methods to monitor internal temperature dynamics within lithium-ion cells swiftly and cost-effectively, alongside a need to develop prognostic techniques to pre-empt thermal runaway occurrences. This study presents an innovative approach that uses ultrasound analysis to track intricate internal temperature fluctuations and gradients within cells. Moreover, an efficient multi-stage warning system is proposed that is designed to proactively prevent thermal runaway events. The findings offer promising avenues for enhancing the safety and reliability of lithium-ion battery systems.